#TITLE_ALTERNATIVE# - SETIAWAN (NIM 20107087), YUDI
The connected resolving number is the minimum cardinality of a connected resolving set in a graph G, denoted by cr(G). In this paper, we determine the metric dimension and the connected resolving number of generalized webs.